2022
DOI: 10.3390/jpm12050801
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Pneumonia Severity Indices, qCSI, 4C-Mortality Score and qSOFA in Predicting Mortality in Hospitalized Patients with COVID-19 Pneumonia

Abstract: This is a retrospective and observational study on 1511 patients with SARS-CoV-2, who were diagnosed with COVID-19 by real-time PCR testing and hospitalized due to COVID-19 pneumonia. 1511 patients, 879 male (58.17%) and 632 female (41.83%) with a mean age of 60.1 ± 14.7 were included in the study. Survivors and non-survivors groups were statistically compared with respect to survival, discharge, ICU admission and in-hospital death. Although gender was not statistically significant different between two groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 72 publications
(130 reference statements)
0
3
0
Order By: Relevance
“…PSI/PORT previously yielded the best performance for in-hospital mortality amongst the general COVID-19 population compared to the qCSI, 4C Mortality Score and quick Sequential Organ Failure Assessment (SOFA) score [31]. This study consistently showed a significant association of PSI/PORT with 30-day post-discharge mortality, but the highest effect size was observed with the 4C Mortality Score.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…PSI/PORT previously yielded the best performance for in-hospital mortality amongst the general COVID-19 population compared to the qCSI, 4C Mortality Score and quick Sequential Organ Failure Assessment (SOFA) score [31]. This study consistently showed a significant association of PSI/PORT with 30-day post-discharge mortality, but the highest effect size was observed with the 4C Mortality Score.…”
Section: Discussionmentioning
confidence: 58%
“…All risk scores were calculated as recommended in the derivation and validation studies, using the appropriate patient-level data [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Elementary data about risk scores are shown in Supplementary Table S1.…”
Section: Risk Scores Of Interestsmentioning
confidence: 99%
See 1 more Smart Citation